2019
DOI: 10.3126/jngmc.v17i2.31659
|View full text |Cite
|
Sign up to set email alerts
|

Antibiotic Sensitivity Pattern of Pathogens Isolated from Pus Culture- A Tertiary Care Hospital Based Study

Abstract: Background: Microbial pathogens cause human skin and soft tissue infections (SSTI) and surgical site infections (SSI) after surgical procedures. These can result in the production of pus, yellowish fluid comprising of dead WBCs and cellular debris. The microorganisms responsible for pus production vary greatly in relation to their spectrum of prevalence in different hospital and also in their antibiotic sensitivity. Further, the antibiotic sensitivity also changes because of the emergence of resistant strains.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 9 publications
4
6
0
Order By: Relevance
“…Even in a blood specimen, the count of E. coli was the highest (n=41, 36.28%) where Simkhada et al in 2016 described Salmonella Paratyphi A (n=26, 54.17%) as the leading etiological agent in blood-borne infections and E. coli is only 6.25% (n=3) (22). The most common isolate in pus specimen was Staphylococcus aureus (n=29, 58%) followed by E. coli (n=8, 16%) which correlates with previous studies (18,23). Although in some instances, E. coli was the most frequently detected bacteria in pus specimens (6,21).…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…Even in a blood specimen, the count of E. coli was the highest (n=41, 36.28%) where Simkhada et al in 2016 described Salmonella Paratyphi A (n=26, 54.17%) as the leading etiological agent in blood-borne infections and E. coli is only 6.25% (n=3) (22). The most common isolate in pus specimen was Staphylococcus aureus (n=29, 58%) followed by E. coli (n=8, 16%) which correlates with previous studies (18,23). Although in some instances, E. coli was the most frequently detected bacteria in pus specimens (6,21).…”
Section: Discussionsupporting
confidence: 84%
“…Children are easily getting infected due to contaminated water and food as well as by contacting contaminated surfaces or animals that may carry certain bacteria like Salmonella spp. (16)(17)(18). Most positive cases were reported in summer-rainy seasons except in pus where the highest count was observed in late autumn.…”
Section: Discussionmentioning
confidence: 96%
“…It has been linked to more trauma care, longer hospitals stay, and treatment. The results revealed 58.28% positivity rate of total sample that correlate with the studies of Rai et al 23 (59%), Trojan et al 8 (60.1%), and Khanam et al 21 (61.8%); however, it exceeded a study conducted by Singh et al 13 (52.73%) and less than a research conducted by Muluye et al 7 (70.2%) and Batra et al 24 (85.02%).…”
Section: Discussionsupporting
confidence: 81%
“…The predominant bacteria isolate recovered in the study included Staphylococcus SPP 44 isolates (30.99%) followed by E coli 41 isolates (28.87%) Klebsiella pneumoniae 23 isolates (16.20%), Pseudomanas aeruginosa 18 isolates (12.68%), Acinetobacter baumanni 9 isolates (6.34%), Enterobacter cloacae 5 isolates (3.52%), Citrobacter koseri 1 isolate (0.70%) and Proteus Mirabilis 1 isolate (0.70%). out of 142 total positive isolates in which gram positive isolate frequency 30.99% and gram negative isolates frequency 69.01%.Singh A et al (2019) 20 found in their study that Staphylococcus SPP 66 isolates (36.1%) were predominant bacteria isolates followed by E coli 44 isolates (24.0%) and then Klebsiella pneumoniae 26 isolates (14.2%). Sahar Mudassar et al (2018) 21 found that Staphylococcus spp 46(4.2%) was the commonest followed by Pseudomonas aeruginosa (19%).…”
Section: Discussionmentioning
confidence: 90%